(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Currently, serological based diagnosis of rice tungro disease (RTD) is being limited by the availability of antisera. This study aims to produce recombinant protein from the coat protein (CP)3 of rice tungro spherical virus (RTSV) as a potential antigen in producing high titre antibodies for use in detection of RTD. Amplified RTSV CP3 gene of approximately 900 bp was cloned into pETSUMO vector. The recombinant plasmid was transformed into cloning host Mach1â„¢-T1Â® E.coli cells and screened for recombinant gene in the correct orientation. Plasmid DNA from positive transformants was isolated and transformed into expression host BL21 (DE3) E.coli cells. One positive clone was selected for large scale expression where the expressed protein was purified and analysed by SDS-PAGE and Western blot. This recombinant RTSV CP3 protein, 46 kDa in molecular mass with 6x His-tag and SUMO protein fused to its N-terminal, was found to be antigenic when it reacted with our in-house generated polyclonal antibodies against tungro viruses.